Peran Pesantren dalam Mengatasi Kemerosotan Moral Era 5.0 - M Imamul Muttaqin; Hilma Alfin Massifa; Fina Hushunul Ahadiyah; Nur Wafiq Maulina Afina; Shevalina Zulfa Falihah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2023)
Pesantren education has existed in Indonesia since before the independence of Indonesia. Pesantren is one of the most famous Islamic educational institutions to date. There are so many roles of pesantren in producing a great Islamic generation that can compete in the world arena. In the current era, moral education is something that is a concern to overcome. To overcome this problem, pesantren education can be a step of change to produce a young generation with Islamic morals. Moral decay in this modern era can be a trigger for negative things to happen in the surrounding environment, so it is very important to instill moral education early on to the nation's next generation.